Obsessions: A Screenplay on Obsessive Compulsive Disorders Impact on Relationships - Putri Patricia Pattiselanno; Ribut Basuki (Institute of Research and Community Outreach - Petra Christian University, 2025)
This creative work explores Obsessive-Compulsive Disorder (OCD) and its impact on relationships, challenging misconceptions and highlighting its complexity. OCD, characterized by intrusive thoughts and repetitive behaviors, significantly affects individuals' well-being and interpersonal dynamics. Despite its prevalence, OCD often faces trivialization, portrayed as quirks rather than a debilitating mental illness. Through Ethan and Ophelia's narrative, this screenplay aims to raise awareness about OCD's effects on relationships. Ethan's struggle underscores challenges faced by individuals and their loved ones, emphasizing the importance of understanding mental health issues and seeking evidence-based treatments like Cognitive Behavioral Therapy (CBT). CBT focuses on modifying maladaptive thinking and behavior patterns through techniques such as recognizing cognitive distortions and developing coping skills. By blending romance and suspense, this work seeks to emotionally engage the audience and foster a compassionate approach to mental health.